Radiographic features of suspected suture‐associated cystic calculi in dogs. Issue 4 (23rd April 2020) - Hickey, Jennifer M.; Berent, Allyson C.; Fischetti, Anthony J.; Le Roux, Alexandre B.
Abstract: This retrospective case series describes the radiographic features of suspected suture‐associated cystic calculi in six dogs with a history of at least one or multiple prior cystotomies. One of the dogs presented twice. Suspected suture‐associated cystic calculi were multifocal, short, predominantly linear mineral opacities localized in the center of the urinary bladder on abdominal radiographs. One patient (n = 1) presented with multifocal round, pin point, and linear radiopaque calculi. The calculi were all calcium oxalate in composition. On gross examination, the calculi had a hollow center. Six cystotomies used monofilament absorbable suture material (polydioxanone [n = 4] or poliglecaprone 25 [n = 1]) in prior cystotomies. Suture material in two of the cases was unknown. Suspected suture‐associated cystic calculi are a rare occurrence in veterinary medicine but should be considered in dogs that have a history of prior cystotomy, hollow core on gross analysis, and radiographic evidence of mineral opaque, predominantly linear, cystic calculi.